2020
DOI: 10.17478/jegys.779438
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a social-emotional learning-based program on self-esteem and self-perception of gifted kindergarten students: A pilot study

Abstract: Social-emotional learning (SEL) and mental health preventive programs are very popular internationally; however, there is limited research evaluating their effects on gifted children. This study aimed to design a SEL-focused preventive program for gifted preschoolers and assess its effects on variables related to personal and character strengths. In addition, the relative differential impact of the program on both genders was explored. The study used an experimental design, with repeated pretest-post-test meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…It seems that adolescents with high scores in these two dimensions tend to feel more positive affect during the self-assessment process and to assess themselves better, which in turn provides them with greater satisfaction with life; that is, the average self-esteem in this process [118]. In kindergarten children, social-emotional learning preventive programs improve selfesteem [119].…”
Section: Self-esteem and Gifted Studentsmentioning
confidence: 99%
“…It seems that adolescents with high scores in these two dimensions tend to feel more positive affect during the self-assessment process and to assess themselves better, which in turn provides them with greater satisfaction with life; that is, the average self-esteem in this process [118]. In kindergarten children, social-emotional learning preventive programs improve selfesteem [119].…”
Section: Self-esteem and Gifted Studentsmentioning
confidence: 99%
“…To be eligible for the study, each gifted child was required to have a signed report from a licensed psychologist certifying that his/her full-scale IQ score was 120 or above according to the Wechsler Preschool and Primary Scale of Intelligence (WPSSI-III-Greek version). This cutoff score has been proposed by other researchers to identify giftedness and for enrollment in services for gifted persons [18,64]. Participants who had been previously diagnosed with any learning disability or mental health condition were excluded from the study.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…The Wechsler Preschool and Primary Scale of Intelligence (WPPSI-III) [65], Greek version [66], is a cognitive ability measure for children aged 2.6-7.3 years that provides an overall ability score (the Full-Scale IQ) and scores on four factor indices: verbal IQ (VIQ), performance IQ (PIQ), processing speed quotient (PSQ), and a general language composite (GLQ). Wechsler scales are commonly used to identify gifted children and to plan psycho-educational services [64]. Scores are reported as standard scores with a mean of 100 and a standard deviation of 15.…”
Section: Measures 221 Cognitive Abilitymentioning
confidence: 99%
“…Topcu Bilir (2019) found that the life skills program had a positive effect on the life skills, self-perception and social emotional adjustment levels of five-year-old children. Papadopoulos (2020) found that the social emotional learning-oriented program applied to gifted children positively affected children's self-perception. Bozkurt Polat et al (2021) concluded that the social skills training program applied to immigrant Afghan children had a positive effect on the development of selfperception.…”
Section: Introductionmentioning
confidence: 97%